Something sleeping in the hall : poems - Kuskin, Karla (N.Y., N.Y. : Harper & Row, 1985)
Poems in humorous vein about animals, nature, friends, and experiences.
"A Charlotte Zolotow book."
Keywords: Children's poetry, American; Humorous poetry; American poetry; Animals -- Poetry